Hydroponic growing of lettuce (Lactuca sativa L.) using a thin layer system with different substrates - Jože OSVALD; Mirjam GANTAR; Nino PETROVIČ (Acta Agriculturae Slovenica)
In the experiment, which took place on the experimental field of the  Bio-technical  Faculty  in Ljubljana from the end of  September 1992 until  February 1993,  we have compared the hydroponic  growing  of lettuce  (cv. 'Lusiana') on four different  substrates  (vermicu-lite, rockwool - 'Agrotervol', compost, and a mixture of compost  and peat)  with classic growing in soil. The highest  average  weight (139.9 g/plant) was measured in the mixture of  compost and peat. The average  weight  in the compost  was 129.3 g/plant, in soil 95.0 g/plant,  in rockwool 72.1 g/plant  and  in  vermiculite  64.4 g/plant.  Plants  grown in vermiculite and rockwool had a much greater  weight  on the upper side of the parcel - at  the  place where  we had been adding nutrient solution - compared  with  the lower  side  of the parcel. Measurement of nitrate on  the  upper side of the parcel registers a higher contain of nitrate in  leaves than in substrates. The highest average nitrate content was  measured in  plants grown in soil, while the lowest average content was recorded in plants  grown in rockwool and in the mixture of compost and peat.